2020
DOI: 10.3390/nano10040667
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Production of Few-Layer Graphene via New-fashioned Strategy Combining Resonance Ball Milling and Hydrothermal Exfoliation

Abstract: Graphene shows great potential applications in functional coating, electrodes, and ultrasensitive sensors, but high-yield and scalable preparation of few-layer graphene (FLG) by mechanical exfoliation method is still a formidable challenge. In this work, a novel two-step method for high-yield preparation of FLG is developed by combining resonance ball milling and hydrothermal treatment. During the resonance ball milling process, the utilization of magnetic Fe3O4 nanoparticles as a new “particle wedge” is benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Wet ball milling uses a surfactant such as N,N-Dimethylformamide (DMF) or N-methyl-2-pyrrolidone (NMP)NMP, which have similar surface energy to that of adjacent graphene flakes and assist in disintegrating graphene layers from graphite. Moreover, dry ball milling is also employed widely to prepare graphene, by milling a mixture of chemically inert water-soluble inorganic salts and graphite followed by washing or sonication steps [ 72 , 73 , 74 ]. In a very recent study, ball milling in series with a shear-mixing exfoliation procedure was used with CO 2 in supercritical condition to produce good-quality FLG, with more than 90% of the produced graphene having less than five layers.…”
Section: Graphene Synthesismentioning
confidence: 99%
“…Wet ball milling uses a surfactant such as N,N-Dimethylformamide (DMF) or N-methyl-2-pyrrolidone (NMP)NMP, which have similar surface energy to that of adjacent graphene flakes and assist in disintegrating graphene layers from graphite. Moreover, dry ball milling is also employed widely to prepare graphene, by milling a mixture of chemically inert water-soluble inorganic salts and graphite followed by washing or sonication steps [ 72 , 73 , 74 ]. In a very recent study, ball milling in series with a shear-mixing exfoliation procedure was used with CO 2 in supercritical condition to produce good-quality FLG, with more than 90% of the produced graphene having less than five layers.…”
Section: Graphene Synthesismentioning
confidence: 99%
“…The main advantage of ball milling production is the possibility of large-scale production, while a drawback is fragmentation and defects, long processing time, high energy consumption, etc. This method is suitable for the production of functionalized graphene for functional coating, energy storage, and electrochemical sensors [61][62][63].…”
Section: Ball Millingmentioning
confidence: 99%
“…In 2008, by using a solvent whose surface energy matches that of graphene, and balancing the energy required to exfoliate graphene with the solvent-graphene interaction, Yenny Hernandez et al demonstrated graphene dispersions up to 0.01 mg ml −1 , which was produced by the dispersion and exfoliation of graphite in N-methyl-pyrrolidone (Hernandez et al, 2008). In 2020, Yang et al developed a two-step method combining resonant ball milling with hydrothermal treatment to prepare few-layer graphene in high yields (Yang et al, 2020). During resonant ball milling, Fe 3 O 4 nanoparticles are used to promote the fragmentation and delamination of graphite layers.…”
Section: Liquid Phase Exfoliationmentioning
confidence: 99%